2004
DOI: 10.1016/j.jvs.2004.08.055
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Prevention of renal failure in patients undergoing thoracoabdominal aortic aneurysm repair

Abstract: Distal aortic and selective renal blood perfusion is an effective measure to protect renal function during TAAA repair, but only if perfusion is provided with adequate volume and pressure. This technique also averts dialysis in most patients with preoperative renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…25,27 Renal failure is related to MOF, 24,25 which has been reported as a common complication after ruptured aortic surgery and is highly correlated with lethal outcome. 8,10,20,21 Preoperative measures to preserve renal function with cooling have been applied previously in thoracoabdominal aortic aneurysm repair 28 and during elective repair of juxtarenal aortic aneurysms 11 with beneficial effects on postoperative renal function. Also, in the current study of RJAA, we observed a tendency toward preservation of renal function and better outcome with the application of cold renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 Renal failure is related to MOF, 24,25 which has been reported as a common complication after ruptured aortic surgery and is highly correlated with lethal outcome. 8,10,20,21 Preoperative measures to preserve renal function with cooling have been applied previously in thoracoabdominal aortic aneurysm repair 28 and during elective repair of juxtarenal aortic aneurysms 11 with beneficial effects on postoperative renal function. Also, in the current study of RJAA, we observed a tendency toward preservation of renal function and better outcome with the application of cold renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance is necessary to ensure that components of the modular system do not migrate and that material fatigue does not cause kinking or fracture of stents. [13][14][15]17,18,27]. The lack of thoracotomy in the endovascular approach likely contributes to the lower rate of pulmonary failure (4.5-6.8%) reported in two published series [21•,37•].…”
Section: Postprocedural Surveillancementioning
confidence: 99%
“…Paraplegia appears most commonly in patients who had prior surgery in another aortic territory and in those with extensive (group II) thoracoabdominal disease. The rate of paraplegia in centers of excellence and in larger-volume series reporting this event is 1-10% [10, 14,18,[24][25][26][27]. The etiology of paraplegia is theorized to be multifactorial, including spinal cord ischemia during surgery and decreased spinal cord perfusion afterward.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations